Kultura organizacyjna w instytucjach kultury - Ablewicz, Joanna (Studia Prawa Publicznego, 2025)
This article discusses one of the most important values nowadays – organisational culture, because what happens inside an organisation is reflected in the goals achieved by the actions it takes. Therefore, organisational culture is important both from the perspective of the recipient of the actions of a cultural institution and its employees, and also that of organising these units themselves. Every organisation creates a certain culture, shaped by all its employees, who decide to accept some and reject other values and norms. Like every organisation, a cultural institution has its own system of values, norms and beliefs, which condition the patterns of thinking and behaviour of its members and are accepted and followed by all or most of its employees and recipients. What matters is that the values supported by the institution’s activities are consistent with those that are important for the social environment. As is rightly emphasized, values can be a source of internal conflicts between employees and the cultural institution if there are discrepancies between the personal value system and the one in force in a given institution. That is why it is crucial to consciously and responsibly define them in the institution’s mission, which will convey a clear message to the environment and potential employees. The implementation of organisational culture was examined using examples of specific acts regulating the activities of individual cultural institutions. Cultural institutions were prove to experience significant problems implementing this value. The statutes, acts and regulations analysed here showed that they often do not define this issue properly.